Evaluasi Kinerja Keuangan PT PLN (Persero) dalam Satu Dekade: Pendekatan Deskriptif dan Naratif - Hidayatullah Hidayatullah; Jalmijn Tindage; Dewi Rosaria (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aimed to evaluate the financial performance of PT PLN (Persero) over the last decade. This study identifies the trends, changes, and factors affecting companies’ financial performance. Research methodology: The methodological approach used in this research was descriptive and narrative. The financial data of PT PLN (Persero) are collected from annual reports, financial statements, and other secondary data sources. Results: This study found that the financial performance of PT PLN (Persero) showed significant variation over the past decade. While there were improvements in some financial ratios, there were also periods of decline caused by internal and external factors, such as regulatory changes, fuel price fluctuations, and government policy changes. These findings indicate the need for more adaptive and innovative management strategies to improve future financial performance. Limitations: This study has several limitations, including the limitation of data covering only one decade and reliance on secondary data that may not accurately reflect the current conditions. Additionally, this research focuses only on financial aspects and does not cover non-financial factors that may affect the performance of PT PLN (Persero). Contribution: This study contributes to the literature on the evaluation of the financial performance of state-owned enterprises (SOEs) in Indonesia, particularly in the energy sector. The findings of this study can be used in the management of PTPLN (Persero) to improve financial and operational strategies.